2018
DOI: 10.1016/j.jedc.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Catching-up and falling behind: Effects of learning in an R&D differential game with spillovers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…We thus observe that for a cooperative solution the number of participating firms may play stabilizing role as long as this number is finite, since this helps to select the regular (thus optimal) equilibrium as an outcome, while if there are infinitely many firms, the regular outcome cannot be reached. This finding agrees with (Bondarev and Greiner 2017), whereas the same claim has been made for decentralized system with symmetric efficiencies but non-linear dynamics. It turns out, that it is the piecewise nature (multiple modes of the game present) of the system which is crucial for the optimality and not the precise type of the underlying dynamical system regimes themselves.…”
Section: It Is Feasible If and Only Ifλsupporting
confidence: 90%
See 3 more Smart Citations
“…We thus observe that for a cooperative solution the number of participating firms may play stabilizing role as long as this number is finite, since this helps to select the regular (thus optimal) equilibrium as an outcome, while if there are infinitely many firms, the regular outcome cannot be reached. This finding agrees with (Bondarev and Greiner 2017), whereas the same claim has been made for decentralized system with symmetric efficiencies but non-linear dynamics. It turns out, that it is the piecewise nature (multiple modes of the game present) of the system which is crucial for the optimality and not the precise type of the underlying dynamical system regimes themselves.…”
Section: It Is Feasible If and Only Ifλsupporting
confidence: 90%
“…This model is close to the setup in (Bondarev and Greiner 2017), where multiple regimes are also obtained, but all players invest with similar efficiency in new products' creation, i. e. ∀k : α − k = α + k = 1. As such that model is a degenerate case 2 of the more general setup considered here.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Henderson [19] found that leading companies invest more in incremental R&D, whereas follower (new entrants) concentrate on fundamental discovery. Bos et al [6] analyzes the nonmonotony of the relationships between various types of innovations throughout the industry life cycle. Henderson and Cockburn [20], Jaffe [21], Hassine et al [2], and more recently Bloom et al [3] conducted empirical studies on spillovers in R&D and found the ambiguous effects of spillovers on innovation.…”
mentioning
confidence: 99%